Real Time Pigging Monitoring System - Abang Masagus, Dayang MishaFazlyiana (2006)
APipeline Inspection Gauge or PIG in the pipeline industry is a tool that is sent down a pipeline and propelled by the pressure ofthe product in the pipeline itself. It is the chief tool used in pigging. This project is called Real Time Pigging Monitoring System, a monitoring system for monitor theprogress of a PIG through a pipeline which often to a high degree ofaccuracy inorder tomaintain the stability ofthe pipeline.